Next generation risk assessment: an ab initio case study to assess the systemic safety of the cosmetic ingredient, benzyl salicylate, after dermal exposure - Ebmeyer, Johanna; Najjar, Abdulkarim; Lange, Daniela; Boettcher, Mareike; Voß, Silja; Brandmair, Katrin; Meinhardt, Jaqueline; Kuehnl, Jochen; Hewitt, Nicola J.; Krueger, Christopher-Tilman; Schepky, Andreas (Frontiers in Pharmacology, 2024)
We performed an ab initio Next Generation Risk Assessment (NGRA) for a fragrance ingredient, benzyl salicylate (BSal), to demonstrate how cosmetic ingredients can be evaluated for systemic toxicity endpoints based on non-animal approaches. New Approach Methodologies (NAMs) used to predict the internal exposure included: skin absorption assays, hepatocyte metabolism, PBPK modelling, and potential toxicodynamic effects were assessed using pharmacology profiling, ToxProfiler Cell stress assay, transcriptomics in HepG2 and MCF-7 cells, ReproTracker DART assays and cytotoxicity assays in human kidney cells. The outcome of the NGRA was compared to the traditional risk assessment approach based on animal data. The identification of the toxicologically critical entity was a critical step that directed the workflow and the selection of chemicals for PBPK modelling and testing in bioassays. The traditional risk assessment and NGRA identified salicylic acid (SA) as the “toxdriver”. A deterministic PBPK model for a single-day application of 1.54 g face cream containing 0.5% BSal estimated the Cmax for BSal (1 nM) to be much lower than its major in vitro metabolite, SA, (93.2 nM). Therefore, SA was tested in toxicodynamics bioassays. The lowest PoDs were from the toxicogenomics assays. The interpretation of these result by two companies and methods were similar (SA only results in significant gene deregulation in HepG2 cells) but the Point of Departure (PoD) differed (213 µM and 10.6 µM). A probabilistic PBPK model for the repeated applications of the face cream estimated the highest Cmax of SA to be 630 nM. The resulting Margin of Internal Exposure (MoIE) using the PoDs were 338 and 16, which were more conservative than those derived from external exposure and in vivo PoDs (Margin of Safety values were 9705). In conclusion, both traditional and ab initio NGRA approaches concluded that the daily application of BSal in a cosmetic leave-on face cream at 0.5% is safe to humans. The processing and interpretation of toxicogenomics data can lead to different PoD, which can subsequently affect the calculation of the MoIE. This case study supports the use of NAMs in a tiered NGRA ab initio approach.